2017
DOI: 10.1002/jbm.a.35972
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the expression of cell cycle genes in osteoblasts and endothelial cells cultured on the surfaces of Ti6Al4V and Ti6Al7Nb alloys

Abstract: Three medically used alloys (Ti6Al4V, Ti6Al7Nb, and AISI 316 L) are compared due to proliferative potential and metabolic response of human cells (osteoblasts line Saos-2 and endothelial cells line EA.hy-926) seeded on the surfaces of these alloys. Although no statistically significant difference in the proliferative potential of the cells cultured on the surfaces of examined biomaterials was observed, it does not exclude relevant differences in metabolic response of these cells assessed as changes in genes' e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…However, contrary to these studies and our results, it has been reported that these two Ti alloy surfaces have no effect on proliferation of human osteosarcoma cells, mesenchymal stem cells, Saos-2 osteoblasts, and EA.hy-926 endothelial cells, and even alloys containing Nb cause cytotoxicity in Saos cells . Of the two alloys containing nanotube films, it has been reported that alloys containing vanadium have better osteoblastic activities .…”
Section: Discussioncontrasting
confidence: 99%
“…However, contrary to these studies and our results, it has been reported that these two Ti alloy surfaces have no effect on proliferation of human osteosarcoma cells, mesenchymal stem cells, Saos-2 osteoblasts, and EA.hy-926 endothelial cells, and even alloys containing Nb cause cytotoxicity in Saos cells . Of the two alloys containing nanotube films, it has been reported that alloys containing vanadium have better osteoblastic activities .…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, there were also specific differences that were clearly visible against the backdrop of a common pattern. The comparison was similar in all other areas of gene expression pattern and it confirms the existence of both specific and nonspecific cell responses to the stress resulting from exposure to artificial surfaces, which has been reported previously by the authors [ 22 , 23 , 24 ] and by others [ 25 , 26 ]. Unfortunately when taking into account transcriptomic analysis of cell response towards biomaterials, in particular titanium alloys, or PEEK, in current literature there is a lack of reports on this topic.…”
Section: Discussionsupporting
confidence: 88%
“…However, some of the genes differed in expression both in relation to the control cells and between cells exposed to individual biomaterials. It has been previously reported that cells are able to recognize and respond to stress resulting from contact with different artificial surfaces in a highly specific manner [ 22 , 23 , 24 ]. Analysis of the results obtained in this study confirms this phenomenon and brings to light several new observations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the amount of proteins adsorbed on the surface, their biological activity, which is connected, for example, with their conformation, may be changed [46,47]. Moreover, the size of the biological molecules and the time of contact with the biomaterial’s surface can determine the tissue–biomaterial interaction [48].…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the fact that the content of Si in the Si-DLC 4 coating is too high and it affects the process of cells’ division. The critical concentration of Si may be different for different cell lines and it may be associated with cellular adaptation [48,53]. Moreover, according to some authors, the high hydrophilicity of surface may inhibit the adhesion of cells due to the preferential adsorption of water molecules [54].…”
Section: Resultsmentioning
confidence: 99%